Mobile based secured student online exam system - Lalitha, V.; Periasamy, J. K. (International Journal of Engineering and Technology, 2018)
Mobile learning is a technology which uses wireless networks and mobile for learning. It facilitates learners to unite their experiences in learning in a collaborative and shared environment. Due to the widespread adoption and use of handheld devices, the mobile application technologies in enhancing learning activities have attracted noteworthy research interest. A Secure Exam Management System (SEMS) is designed for mobile environment and to simplify the exam management system. The teachers will define a bank of exam questions and link them to his/her subject through an appropriate interface (Subject‘s Question Bank Interface). The students can enter the exam system at the pre-defined date and time through the Exam Enrollment Interface. The students scan the QR code in the electronic device (Mobile/tablet) and then view an exam question in the same interface. Asthe school Wi-Fi network is connected to the students mobile or tablet, turning the network down during exams canavoid malpractice. Multifactor authentication can be adopted for stronger security.